Is the Public Investment Multiplier Higher in Developing Countries? : An Empirical Exploration - Izquierdo, Alejandro (IMF Working Papers; Working Paper ;, 2019)
Over the last decade, empirical studies analyzing macroeconomic conditions that may affect the size of government spending multipliers have flourished. Yet, in spite of their obvious public policy importance, little is known about public investment multipliers. In particular, the clear theoretical implication that public investment multipliers should be higher (lower) the lower (higher) is the initial stock of public capital has not, to the best of our knowledge, been tested. This paper tackles this empirical challenge and finds robust evidence in favor of the above hypothesis: countries with a low initial stock of public capital (as a proportion of GDP) have significantly higher public investment multipliers than countries with a high initial stock of public capital. This key finding seems robust to the sample (European countries, U.S. states, and Argentine provinces) and to the identification method (Blanchard-Perotti, forecast errors, and instrumental variables). Our results thus suggest that public investment in developing countries would carry high returns.